Mitigating Membrane Fouling in Abattoir Wastewater Treatment: Integration of Pretreatment Step with Zwitterion Modified Graphene Oxide–Polyethersulfone Composite Membranes - Meladi L. Motloutsi; Funeka Matebese; Mxolisi M. Motsa; Muthumuni Managa; Richard M. Moutloali (Membranes)
Composite polyethersulfone (PES) membranes containing N-aminoethyl piperazine propane sulfonate (AEPPS)-modified graphene oxide (GO) were integrated with either of the two pretreatment processes (activated carbon (AC) adsorption or polyelectrolyte coagulation) to assess their effectiveness in mitigating membrane fouling during the treatment of abattoir wastewater. The AEPPS@GO-modified membranes, as compared to the pristine PES membranes, showed improved hydrophilicity, with water uptake increasing from 72 to 118%, surface porosity increasing from 2.34 to 27%, and pure water flux (PWF) increasing from 235 to 673 L.m−2h−1. The modified membranes presented improved antifouling properties, with the flux recovery ratio (FRR) increasing from 59.5 to 93.3%. This study compared the effectiveness of the two pretreatment processes, AC, coagulation, and the integrated system (coagulation/AC-UF membrane), in the removal of natural organic matter (NOM) and improvement of abattoir wastewater’s pH, electrical conductivity, TDS, and turbidity. The integrated systems produced improved water quality in terms of pH, EC, TDS, turbidity, and organic content. The fluorescence excitation–emission matrix (FEEM) analysis exhibited almost no fluorescence peak post-treatment following organic loading removal. The quality of the water met the South African non-potable water reuse standards. The sole membrane treatment systems exhibited good fouling resistance without the pretreatment systems; however, integrating these systems can offer extended longer filtration periods, thereby assisting in cost aspects of the abattoir wastewater treatment system.